Irisin: A Potential Link between Physical Exercise and Metabolism—An Observational Study in Differently Trained Subjects, from Elite Athletes to Sedentary People. (13th March 2017) - Benedini, Stefano; Dozio, Elena; Invernizzi, Pietro Luigi; Vianello, Elena; Banfi, Giuseppe; Terruzzi, Ileana; Luzi, Livio; Corsi Romanelli, Massimiliano Marco
Abstract : We compared irisin levels among groups of differently trained healthy individuals to explore the role of irisin as a physiological linker between exercise and metabolic health. Irisin and biochemical parameters of glucose and lipid metabolism were assessed in 70 healthy volunteers stratified for sport performance level into four groups: (1 ) 20 elite athletes of national level, (2 ) 20 subelite athletes of local level, (3 ) 20 recreational athletes, and (4 ) 10 sedentary subjects. All biochemical parameters were within the ranges of normality. Fasting glucose, HOMA-IR, and total cholesterol levels were inversely related to the degree of physical activity. HbA1c was higher in elite athletes compared to all the other groups (p < 0.01 ). A U-shaped relation between free fatty acids and the degree of physical activity was observed. All groups showed similar plasma irisin levels. After correction for the degree of insulin resistance (irisin/HOMA-IR), elite athletes showed higher levels compared to sedentary and recreational subjects (p < 0.01 and p < 0.05, resp.). In addition, the number of metabolic parameters correlated with irisin increased at increasing the training status. Our study suggests a correlation between sport performance, insulin sensitivity, and irisin levels. Irisin may be one potential mediator of the beneficial effects of exercise on metabolic profile.